Development of novel phase change material (PCM)-based nanocomposites using emerging nanomaterials for energy storage applications / Navid Aslfattahi - Navid , Aslfattahi (2021)
Energy storage is a global critical issue and important area of research as most of the renewable sources of energy are intermittent. In this thesis, novel nanomaterials including recently emerged two-dimensional nanomaterial MXene (Ti3C2), hybrid graphene-silver (Gr-Si), hexagonal boron nitride (hBN), magnesium oxide (MgO) and alumina (Al2O3) nanoparticles are used as additives into various types of organic/inorganic phase change materials (PCMs) for formulation of promising PCM-based nanocomposites to improve their thermo-physical properties. This research work focuses on synthesis, preparation, characterization, thermal storage properties and thermal stability characteristic of new class of nanocomposites induced with advanced/emerging nanomaterials. Novel two_dimensional MXene (Ti3C2) nanomaterial is synthesized experimentally in laboratory using wet-chemical etching method through in-situ preparation of hydrofluoric acid incorporating two types of fluoride salts. Conducted structural analysis including XRD and Raman spectroscopy analysis confirmed the purity of the as-synthesized two_dimensional Ti3C2 nanomaterial. Thermal energy storage properties of the developed novel organic/inorganic PCM-based nanocomposites have been measured at elevated temperatures using differential scanning calorimetry analysis. It is evident experimentally that the PW70/MXene nanocomposite with loading concentration of 0.3 wt.% shows the improvement of thermal energy storage property by ~43%. The experimentally achieved specific heat capacity (cp) results for hybrid PCM/Graphene-Silver nanocomposites with loading concentration of 0.3 wt.% shows promising improvement of thermal energy storage property by ~40%. The measured average cp value of the synthesized binary PCM-based hBN nanocomposite with the highest loading concentration of 1.5 wt.% represented promising enhancement of ~180%. Enthalpy of the binary nitrate based PCM/MgO nanocomposites decreased by 12.4% which proves more exothermic reaction in melting point. The experimental methods for synthesized eutectic ternary nitrate based PCM/Alumina nanocomposite showed that the enthalpy increased by 16.5% by the introduction of 1 wt.% of Al2O3 nanoparticles. Conducted experiments for palmitic acid PCM/MXene nanocomposites revealed enhancement in enthalpy by 10.3%. It was also found that 25.8% increase in volumetric specific heat capacity of the developed nanocomposite (palmitic acid PCM/MXene) makes it suitable for TES applications. Assessment of the thermal degradation for all of the synthesized PCM-based nanocomposites is conducted by using thermo-gravimetric analysis method. The focal degradation temperature of PW70/MXene nanocomposite with loading concentration of 0.3 wt.% is found to be 384 °C with ~6% improvement. Thermal durability measurements for hybrid PCM/Graphene-Silver nanocomposites revealed that the weight loss occurs within the temperature range from 263 to 424 °C. Developed binary nitrate PCM-based hBN nanocomposite with loading concentration of 1.5 wt.% represented ~16% enhancement in thermal stability. The experimentally acquired results revealed the increment of decomposition temperature from 734.29 to 750.73 °C for the binary nitrate based PCM/MgO nanocomposite. It is found that ternary nitrate-based PCM/Alumina nanocomposite with loading concentration of 1 wt.% reached the focal degradation temperature of 694 °C. Thermal degradation temperature of the developed palmitic acid PCM/MXene nanocomposite enhances from 270 ⁰C to 305 ⁰C by introduction of 0.3 wt.% of Ti3C2 nanomaterial. The experimentally achieved improvements in thermo-physical properties reveals the beneficial aspects of the developed organic/inorganic PCM-based nanocomposites in thermal energy storage applications.